Exploring antecedents of employees turnover intention in telecommunication company: the role of transformational leadership and employee engagement. - Prasetio, Arif Partono; Luturlean, Bachruddin Saleh; Sari, Olvia Fitri Dewi Puspita (International Journal of Psychosocial Rehabilitation, 2020)
The current study examines the relationship between transformational leadership and the employee’s turnover intention and the mediation role of engagement. Leaders who perform a transformational style believed to provide great vision, guidance, and build positive relations which can drive their follower to develop higher motivation, commitment and more attached to the organization so they will engage beyond their job description. Employee turnover intention usually affected by an how deep the employee engages in their job and the relation with their supervisor. An individual who is firmly engaged with the organization will stay longer and demonstrate higher performance. This cross-sectional study using a sample of 150 participants from a telecommunication company in Indonesia. SPSS 21 and Macro Process was used for data analysis and result interpretation. Results reveal that there is a significant negative influence of transformational leadership on employee engagement and the employee’s turnover intention. Transformational leadership also found to have positive link with employee engagement. Thus, engagement mediated the linkage between transformational and turnover intention. This empirical study provides a thorough explanation regarding the correlation between variables. Future studies using wider participants from across Indonesia can be conducted to reflect cultural differences among other provinces.